Atherosclerotic cardiovascular disease in patients with chronic inflammatory joint disorders. Issue 10 (17th February 2016) - Agca, R; Heslinga, S C; van Halm, V P; Nurmohamed, M T
Abstract : Inflammatory joint disorders (IJD), including rheumatoid arthritis (RA), ankylosing spondylitis (ASp) and psoriatic arthritis (PsA), are prevalent conditions worldwide with a considerable burden on healthcare systems. IJD are associated with increased cardiovascular (CV) disease-related morbidity and mortality. In this review, we present an overview of the literature. Standardised mortality ratios are increased in IJD compared with the general population, that is, RA 1.3–2.3, ASp 1.6–1.9 and PsA 0.8–1.6. This premature mortality is mainly caused by atherosclerotic events. In RA, this CV risk is comparable to that in type 2 diabetes. Traditional CV risk factors are more often present and partially a consequence of changes in physical function related to the underlying IJD. Also, chronic systemic inflammation itself is an independent CV risk factor. Optimal control of disease activity with conventional synthetic, targeted synthetic and biological disease-modifying antirheumatic drugs decreases this excess risk. High-grade inflammation as well as anti-inflammatory treatment alter traditional CV risk factors, such as lipids. In view of the above-mentioned CV burden in patients with IJD, CV risk management is necessary. Presently, this CV risk management is still lacking in usual care. Patients, general practitioners, cardiologists, internists and rheumatologists need to be aware of the substantially increased CV risk in IJD and should make a combined effort to timely initiate CV risk management in accordance with prevailing guidelines together with optimal control of rheumatic disease activity. CV screening and treatment strategies need to be implemented in usual care.